National Evaluation of the Domestic Violence Victims' Civil Legal Assistance (CLA) Program, 1997-2003 (United States) - Connors, Edward ([Verlag nicht ermittelbar], 2010)
The national evaluation of the Legal Assistance for Victims (LAV) program had three main objectives: (1) to document the range of local activities and programs supported by the Fiscal Year 1998 to Fiscal Year 2000 LAV grants, (2) to conduct a process evaluation by examining and documenting LAV grantee planning and implementation efforts, and (3) to evaluate the effectiveness of LAV programs in meeting the needs of the victims they serve. A mixed method approach was developed to conduct the evaluation. The researchers used a classic triangulation framework of quantitative agency data, telephone survey interviews, mail surveys, interviews and focus groups with service providers, and case studies. The evaluation of effectiveness included (1) before-after analysis of caseload data on 88,901 clients and (2) interviews with 124 LAV clients. The range of local activities and programs was documented primarily through two mail surveys of grantees. For Part 1 (2001 Mail Survey), data include information regarding project staffing, partnerships, legal and advocacy services provided, and implementation challenges. It was completed by 156 grantees. Part 2 (2003 Mail Survey) was administered to the 2001 survey respondents who had also received continuation grants in 2001 or 2002. It was completed by 79 grantees. This survey sought information on successful practices for achieving key project objectives. It also attempted to quantify the number and types of legal services provided and gain more quantitative information on unmet needs. Part 3 (Legal Assistance for Victims Data) contains caseload data including demographics related to clients such as gender, ethnicity, and income. It also contains information regarding the case including type of case, hours worked on the case, and results of the case. There are also data related to the agency such as jurisdiction of the agency and type of agency. For Part 4 (Victims Interviews), data include demographic information, history and background of the case, legal services received, satisfaction with legal services, impact of legal services, and the victim's current situation.